Transformation of collective intelligences. Volume 2, Perspective of transhumanism - Noyer, Jean-Max (London : ISTE ; Hoboken, NJ : Wiley, 2016)
There is a great transformation of the production of knowledge and intelligibility. The "digital fold of the world" (with the convergence of NBIC) affects the collective assemblages of "thought", of research. The aims of these assemblages are also controversial issues. From a general standpoint, these debates concern "performative science and performative society". But one emerges and strengthens that has several names: transhumanism, post-humanism, speculative post-humanism. It appears as a great narration, a large story about the future of our existence, facing our entry into the Anthropocene. It is also presented as a concrete utopia with an anthropological and technical change. In this book, we proposed to show how collective intelligences stand in the middle of the coupling of ontological horizons and of the "process of bio-technical maturation."
Front Matter -- Elements of the General Configuration and Adaptive Landscape of Collective Intelligences -- Post- and Transhumanist Horizons -- Fragmented Encyclopedism -- Bibliography -- Index -- Other titles from iSTE in Information Systems, Web and Pervasive Computing.
Intellectual technologies set, coordinated by Jean-Max Noyer and Maryse Carmes.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Artificial intelligence; Artificial Intelligence; Intelligence artificielle; artificial intelligence; COMPUTERS -- General; Artificial intelligence